Evaluation of the antioxidant effects in vitro of the isopulegone - Silva, Oskar Almeida; Oliveira, Francisco Rodrigo de Asevedo Mendes de; Lima, Tamires Cardoso; Sousa, Damião Pergentino de; Souza, Alexandre Araújo de; Freitas, Rivelilson Mendes de (Free Radicals and Antioxidants)
Background: Studies report that monoterpenes and their synthetic derivatives have diverse biological and pharmacological properties. Among these compounds, isopulegone present in the essential oil of various aromatic plants have been used in the production of cosmetics. Objectives: evaluated the antioxidant properties of (-)-isopulegone in vitro against the formation of reactive species using the tests thiobarbituric acid (TBARS), hydroxyl radical and nitric oxide production. Materials and Methods: The (-)-isopulegone was tested at different concentrations (0.9, 1.8, 3.6, 5.4, 7.2 µg/mL), and compared with trolox (positive control). We evaluated the level of lipid peroxidation induced by 2,2’-azobis-2- methyl-propanimidamide dihydrochloride (AAPH) by the amount of TBARS formed. We evaluated the in vitro effects of (-)-isopulegone against hydroxyl radical formation from Fenton reaction. In assessing production of nitric oxide, was used sodium nitroprusside on decomposition. Results: (-)-Isopulegone in the concentrations tested, was capable of preventing lipid peroxidation induced by AAPH, reducing the amount of TBARS formed. The hydroxyl radical formation was inhibited, suggesting a possible antioxidant action of this monoterpene. In the evaluation of the production of nitric oxide isopulegone decreased the formation of such compound, showing a shield in vitro profile of biomolecules such as lipids of the cell membranes from damage caused by free radicals generated. The (-)-isopulegone demonstrated strong antioxidant potential in vitro, by removal capacity against hydroxyl radicals and nitric oxide, and prevented the formation of TBARS, similarly to trolox (positive control). Conclusion: However, further studies are needed to better characterize the antioxidant properties of (-)-isopulegone, especially prominently in vitro.
Keywords: Essential oil; Hydroxyl radical; Lipid peroxidation; Monoterpene; Nitric oxide